2015
DOI: 10.1007/s13181-015-0498-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Observation Units for the Care of Poisoned Patients: Trends from the Toxicology Investigators Consortium Case Registry

Abstract: Many poisoned patients may only require a period of observation after their exposure. There are limited data describing the use of observation units for managing poisoned adult and pediatric patients. We performed a retrospective review of all patients reported to the ToxIC Case Registry between January 1, 2012 and December 31, 2013. Eligible patients included those who received a bedside consultation by a medical toxicologist and whose care was provided in an observation unit, or those who were admitted under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Previous single-center studies (11–16) have identified predictors similar to the findings in our model to determine whether children may be safely monitored in a short-stay observation unit outside of the PICU (17, 18). Clonidine and antidiabetic medications were significant in our multivariable models for children under 6 years old.…”
Section: Discussionmentioning
confidence: 65%
“…Previous single-center studies (11–16) have identified predictors similar to the findings in our model to determine whether children may be safely monitored in a short-stay observation unit outside of the PICU (17, 18). Clonidine and antidiabetic medications were significant in our multivariable models for children under 6 years old.…”
Section: Discussionmentioning
confidence: 65%
“…In 2016, 14 abstracts and five manuscripts using ToxIC Registry data were published and are listed on http://www. ToxICRegistry.org (Farrugia et al [2]; Beauchamp et al [3]; Judge et al [4]; Riederer et al [5]; Wang et al [6]).…”
Section: Introductionmentioning
confidence: 99%
“…7 27,28 acil durumda hızlı müdahale eden takımların oluşturulması ve ekip çalışması sayesinde, 9 pek çok hastanın çocuk genel servisi içerisinde güvenle takip edilebileceği düşünülmektedir. 7,29 Çocuklara yönelik zehirlenme şiddet ve risk skorlarının geliştirilmesi ile hangi hastanın yoğun bakım ünitesi yatışına ihtiyaç duyacağının belirlenmesi önem kazanmaktadır. Yetişkinlerde, zehirlenmenin şiddetini ve yoğun bakım ihtiyacını öngörecek, başvuru anındaki bulgular ve klinik takiplere dayanarak oluşturulan risk skorları mevcuttur.…”
Section: Bulgularunclassified